2007
DOI: 10.1007/s10562-007-9263-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Catalytic Activity of Palladium Nanoparticles Encapsulated in SBA-15

Abstract: A simple adsorption method was studied for the preparation of SBA-15-encapsulated palladium nanoparticles. This method employed the SBA-15 with organic template removed by ethanol extraction for the adsorption of cationic Pd precursors in alkaline solution followed by calcination and H 2 reduction. The pH of the solution was found to be a critical factor in determining the palladium content and the ordered mesoporous structure. Our characterizations revealed that the Pd nanoparticles prepared by this method we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 36 publications
1
32
1
1
Order By: Relevance
“…Nevertheless, for the heterogeneous Pd-catalyzed oxidation of alcohols, Pd(0) has been proposed as the active phase in many systems. [7,8,[11][12][13][14][15][16] Solid evidence has been obtained to support this in some research papers. For examples, Mori et al [7b] have confirmed that Pd species over hydroxyapatite are transformed to Pd(0) nanoparticles after the oxidation of 1-phenylethanol via EXAFS measurements; Grunwaldt et al [8] have clarified that the metallic Pd over Al 2 O 3 support is much more active (over 50 times) for the aerobic oxidation of benzyl alcohol than the oxidic Pd species.…”
Section: Structure-sensitivity Of Pd Nanoparticles-catalyzed Oxidatiomentioning
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, for the heterogeneous Pd-catalyzed oxidation of alcohols, Pd(0) has been proposed as the active phase in many systems. [7,8,[11][12][13][14][15][16] Solid evidence has been obtained to support this in some research papers. For examples, Mori et al [7b] have confirmed that Pd species over hydroxyapatite are transformed to Pd(0) nanoparticles after the oxidation of 1-phenylethanol via EXAFS measurements; Grunwaldt et al [8] have clarified that the metallic Pd over Al 2 O 3 support is much more active (over 50 times) for the aerobic oxidation of benzyl alcohol than the oxidic Pd species.…”
Section: Structure-sensitivity Of Pd Nanoparticles-catalyzed Oxidatiomentioning
confidence: 92%
“…[13,14] Pd nanoparticles located in zeolite NaX or mesoporous silica SBA-15 could catalyze the solvent-free aerobic oxidation of several kinds of alcohols. [15,16] A Pd-Au/TiO 2 catalyst could give excellent TOFs for the aerobic oxidation of various alcohols, and it was suggested that the Au-Pd nanocrystals made of an Au-rich core with a Pd-rich shell accounted for the superior catalytic performances of this catalyst. [17] It is well known that catalytic performances can be very sensitive to the size of the active phase.…”
Section: Introductionmentioning
confidence: 99%
“…[47] The synthesis is based on the adsorption of a cationic Pd precursor at pH 8-11 onto the negatively charged surface of non-calcined SBA-15, followed by calcination at 550 8C and reduction of Pd II in H 2 at 300 8C. Clearly, the pH of the solution played a key role in the adsorption of the Pd precursor onto the support.…”
Section: Palladiummentioning
confidence: 99%
“…All samples exhibit one intense peak at 0.8-1.0 • along with two weak peaks at 1.3-2.0 • , which can be assigned to the (1 0 0), (1 1 0), and (2 0 0) plane reflections of the two-dimesional hexagonal mesostructure with a space group of p6mm symmetry [29], indicating that the incorporation of Pd has negligible influence on the original structure of SBA-15. However, the intensities of these diffraction peaks have a slight decrease for samples synthesized via the grafting approach, indicating that the mesoporous channels of SBA-15 may be occupied by Pd nanoparticles [23]. By carefully comparing the patterns in Fig.…”
Section: Samplementioning
confidence: 99%
“…8.2 nm). Zhang and co-workers [23] 0304-3894/$ -see front matter © 2010 Elsevier B.V. All rights reserved. doi:10.1016/j.jhazmat.2010.05.113 prepared highly dispersed Pd/SBA-15 catalysts (Pd size = 3-4 nm) using a simple adsorption method under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%